Perception of ethics committee members and investigators on implementation of e-EC software for ethics committees - Shetty, Yashashri; Marathe, Padmaja; Lad, Manasi; Auti, Prajakta; Katkar, Janhavi; Singh, Vishal (International Journal of Clinical Trials, 2024)
Background: An e-EC software (Create 4) was introduced since past 4 years at few institutional ethics committees (EC) in India. The software provided facilities for submission, online review and communication between investigator and EC. The study was to assess the perception of different stakeholders: investigators, chairperson, member secretary (MS), EC members, administrative staff regarding their experiences of using software, challenges faced and recommendations for improvisation. Methods: Following approval of the institutional EC, the participants were enrolled after obtaining their written informed consent. The questionnaires specifically designed and validated for each category of investigators, EC members and administrative staff were administered. Strict confidentiality was maintained. The data was analysed using descriptive statistics. Results: A total of 64 stakeholders who participated, there were 34 investigators, 18 EC members, 2 Chairpersons, 4 member secretaries, 6 administrative staff. The e-software was accepted well by majority of the stakeholders. Overall, the software was found to be user-friendly. A few challenges faced were: lack of adequate training for investigators and new EC members, inconvenience faced while downloading study documents one by one and the need to ensure uninterrupted internet access at workplace. The user ECs should ensure that the investigators and EC members are tech-savvy and they receive prior training. It was suggested that there needs to be an autofill option built-in while uploading document/s. Conclusions: E-software was found to be useful by the stakeholders and provided suggestions to optimize its us.